Test of the Validity and Reliability of Mental Health in Preventing Bullying Through Positive Behavior in Adolescents - Choirulloh, Alvin; Alfianto, Ahmad Guntur; Muntaha; Ulfah, Miftahul (KHD-Production, 2024)
Mental health is one of the negative behaviors in teenagers such as bullying. Bullying can cause teenagers to become anxious, depressed, sleep disorders, angry, and at risk of suicide. To find out this, developing an instrument for positive adolescent behavior in preventing bullying is necessary. This research aims to test the validity and reliability of the questionnaire. Questionnaire Positive Behavior Support Quality of Life Questionnaire (PBSQLQ) in Indonesian. The method used is testing a questionnaire PBSQLQ in Indonesian with a quantitative approach and cross-sectional design. The sample was 30 teenagers living in Malang Regency using an incidental sampling technique. PBSQLQ results in Indonesian have five indicators, namely health and safety (Cronbach alpha = 0.961), self-advocacy (Cronbach alpha = 0.831), social relationships (Cronbach alpha = 0.852), productive activities (Cronbach alpha = 0.741), and community participation (Cronbach alpha = 0.755). The validity test results of all indicator questions were declared valid. Analysis of questionnaires about positive behavior in preventing bullying in teenagers using PBSQLQ in Indonesian can be used as a measuring tool for mental health research in teenagers due to bullying. So, this questionnaire can be used as an indicator of the positive behavior of teenagers in preventing bullying, especially on the impact on mental health in teenagers. This research concludes that the PBSQLQ in Indonesian has a valid value for each question per indicator and has a reliable or consistent value as a tool for measuring positive behavior in preventing bullying in teenagers.